Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=x^2+y^2+1-2x-2y+2xy-4\)
\(=\left(x+y-1\right)^2-2^2\)
\(=\left(x+y-3\right).\left(x+y+1\right)\)
\(x^2+y^2-2x-2y+2xy-3\)
\(=x^2+y^2+1-2x-2y+2xy-4\)
\(=\left(x+y-1\right)^2-2^2\)
\(=\left(x+y-3\right).\left(x+y+1\right)\)
1, x2(x2+2x+1)=x2(x+1)2
2, 2(x2+2x+1-y2)=2(x+1-y)(x+1+y)
3, 16-(x2+2xy+y2)=(4-x-y)(4+x+y)
\(x^4+2x^3+x^2\)
\(=x^2\left(x^2+2x+1\right)\)
\(=x^2\left(x+1\right)^2\)
hk tốt
^^
a) \(2x-2y-x^2+2xy-y^2\)
\(=2\left(x-y\right)-\left(x^2-2xy+y^2\right)\)
\(=2\left(x-y\right)-\left(x-y\right)^2\)
\(=\left(x-y\right)\left(2-x+y\right)\)
b) \(9x^2+6xy+y^2-25\)
\(=\left(3x\right)^2+6xy+y^2-25\)
\(=\left(3x+y\right)^2-5^2\)
\(=\left(3x+y+5\right)\left(3x+y-5\right)\)
Sửa đề :
\(x^3+y^3+2x^2+2xy\)
\(=\left(x^3+y^3\right)+\left(2x^2+2xy\right)\)
\(=\left(x+y\right)\left(x^2-xy+y^2\right)+2x\left(x+y\right)\)
\(=\left(x+y\right)\left(x^2-xy+y^2+2x\right)\)
a) \(9x^2-12x+4\)
\(=9x^2-6x-6x+4\)
\(=3x\left(3x-2\right)-2\left(3x-2\right)\)
\(=\left(3x-2\right)^2\)
b) \(2xy+16-x^2-y^2\)
\(=-\left(x^2-2xy+y^2-16\right)\)
\(=-\left(x-y\right)^2+16\)
\(=\left(4-x+y\right)\left(4+x-y\right)\)
c) \(3x+2x^2-2\)
\(=2x^2+4x-x-2\)
\(=2x\left(x+2\right)-\left(x+2\right)=\left(x+2\right)\left(2x-1\right)\)
a. x4 - 27x = x ( x3 - 33 ) = = x ( x - 3 ) ( x2 + 3x + 32 ) = x ( x - 3 ) ( x2 + 3x + 9 )
b. x3 + 2x2 + 2x + 1 = ( x3 + 13 ) + ( 2x2 + 2x ) = ( x + 1 ) ( x2 - x + 1 ) + 2x ( x + 1 ) = ( x + 1 ) ( x2 + x + 1 )
c. 4x - 4y + x2 - 2xy + y2 = 4 ( x - y ) + ( x - y )2 = ( x - y ) ( x - y + 4 )
a
\(x^4-27x\)
\(=x\left(x^3-27\right)\)
\(=x\left(x^3-3^3\right)\)
\(=x\left(x-3\right)\left(x^2+3x+9\right)\)
b
\(x^3+2x^2+2x+1\)
\(=x^3+x^2+x^2+x+x+1\)
\(=x^2\left(x+1\right)+x\left(x+1\right)+1\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2+x+1\right)\)
c
\(4x-4y+x^2-2xy+y^2\)
\(=4\left(x-y\right)+\left(x-y\right)^2\)
\(=\left(x-y\right)\left(x-y+4\right)\)
1) Ta có: 2xy - x2 - y2 + 16
= -(x2 - 2xy + y2 - 16)
= -[(x - y)2 - 16]
= -(x - y - 4)(x - y + 4)
2) x3 + 2x2y + xy2 - 9x
= x(x2 + 2xy + y2 - 9)
= x[(x + y)2 - 9]
= x(x + y - 3)(x + y + 3)
3) x4 - 2x2 = x2(x2 - 2)
1. 2xy-x2-y2+16= -(x2-2xy+y2-16) = -(x2-2xy+y2)-16 = -(x-y)2-16= (x+y)2-42= (x+y-4).(x+y+4)
2. x3+2x2y+xy2-9x= (có sai đề không vậy?)
a) 2x - 2y - x2 + 2xy - y2
Ta có:2.(x-y)-(x2-2xy+y2)
=2.(x-y)-(x-y)2
=2.(x-y)-(x-y)(x-y)
=(x-y)[2-(x-y)]
b)x4-2x2
Ta có:x4-2x2
=x2.(x2-2)
=x2.(x2-\(\left(\sqrt{2}\right)^2\))
=x2.(x-\(\sqrt{2}\))(x+\(\sqrt{2}\))
c)x4+4
Ta có:x4+4
=(x2)2+22+2.x2.2-4x2
=(x2+2)2-(2x)2
=(x2+2+2x)(x2+2-2x)
\(b,x^2+y^2-2x-2y-2xy\)
\(=\left(x-y\right)^2-2\left(x-y\right)\)
\(=\left(x-y\right)\left(x-y-2\right)\)
\(=\left(2xy+1+2x+y\right)\left(2xy+1-2x-y\right)\)
\(=\left[2x\cdot\left(y+1\right)+y+1\right]\cdot\left[2x\cdot\left(y-1\right)-\left(y-1\right)\right]\)
\(=\left(2x+1\right)\cdot\left(y+1\right)\cdot\left(2x-1\right)\cdot\left(y-1\right)\)
\(=\left(4x^2-1\right)\cdot\left(y^2-1\right)\)
\(\left(2xy+1\right)^2-\left(2x+y\right)^2\)
\(=\left(2xy+1-2x-y\right)\left(2xy+1+2x+y\right)\)
\(=\left[2x\left(y-1\right)-\left(y-1\right)\right]\left[2x\left(y+1\right)+\left(y+1\right)\right]\)
\(=\left(y-1\right)\left(2x-1\right)\left(y+1\right)\left(2x+1\right)\)